2017
DOI: 10.1016/j.ijid.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in extrapulmonary tuberculosis

Abstract: Tuberculosis (TB) remains a major global public health problem, with 1.5 million deaths annually worldwide. One in five cases of TB present as extrapulmonary TB (EPTB), posing major diagnostic and management challenges. Mycobacterium tuberculosis adapts to a quiescent physiological state and is notable for its complex interaction with the host, producing poorly understood disease states ranging from latent infection to active clinical disease. New tools in the diagnostic armamentarium are urgently required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 47 publications
2
101
0
3
Order By: Relevance
“…All studies showed significant uptake of FDG or increased SUVmax value in active TB; which resembles with this present study. Hence, 18 F FDG PET-CT imaging may play a potential role in the localization lesions and extension of the EPTB (3,6,7,8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies showed significant uptake of FDG or increased SUVmax value in active TB; which resembles with this present study. Hence, 18 F FDG PET-CT imaging may play a potential role in the localization lesions and extension of the EPTB (3,6,7,8).…”
Section: Resultsmentioning
confidence: 99%
“…The test has limitations of being falsely negative in immunocompromised patients, while it gives false-positive results are seen in patients with other types of mycobacteriosis or history of previous vaccinations against TB (3). TB blood tests are also called interferon-gamma release assays or IGRAs that uses a blood sample to find out if someone is infected with TB bacteria, but it cannot differentiate between active and latent TB (5,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging techniques such as ultrasound, CT or magnetic resonance imaging of the neck are useful for initial evaluation of lymphadenopathy and can identify the lymph node group most suitable for biopsy, as well as assist in the biopsy [5] . The “gold standard” for diagnosis remains the culture, although it may take up to 3 to 4 weeks to yield results, which represents a major delay in establishing the diagnosis when malignant processes need to be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In advance disease it may cause obstructive uropathy, bladder defect and loss of kidney function leading to chronic renal failure. Diagnostic imaging may show calcification, distorted ureters with alternate stenosis and dilatation, reduced bladder volume, hydro-nephrosis, chalice distortion, cavities and decreased kidneys size and function in advance disease [8,9].…”
Section: Discussionmentioning
confidence: 99%